Failure prediction of fissured rock under freeze-thaw cycles based on critical slowing down theory of acoustic emission multi-parameter - Xiaodie Liang; Zhixiang Liu; Kang Peng; Houqiang Wang; Shuangxia Zhang; Congxiang Yuan (Results in Engineering)
Fissured rocks in cold regions are affected by freeze-thaw (FT) cycles and stress disturbances, posing significant challenges to engineering projects in these areas. Understanding and identifying the failure precursor characteristics of fissured rocks under FT cycles is crucial for ensuring mining safety. Therefore, in this study, quasi-static compression tests were performed on fissured sandstone under FT cycles, utilizing acoustic emission (AE) monitoring and digital image correlation (DIC) systems to capture the failure characteristics. The results indicated that FT cycles and fissure angles affect the failure patterns by increasing the internal structural defects and influencing the stress geometry distribution conditions, respectively. The sudden increase in AE count and AE energy, along with the abrupt decrease in b-value, effectively reflected the failure of the specimens, while RA-AF values revel the evolution of crack types. Then, based on the critical slowing down (CSD) theory, the variance (Var) and autocorrelation coefficient (A) curves of the AE multi-parameters were analyzed. The sudden increases in Var and A could indicate impending specimen failure. Compared to the A-curves, the Var-curves have fewer false signals, are more sensitive, and can be used as the primary criterion for early warning of rock failure. Finally, the timeliness and reliability of the AE multi-parameter CSD theory for predicting the failure of fissured rocks are verified using the results of AE tests.